Aging, probability weighting, and reference point adoption: An experimental study - Ayako Suzuki; Koichi Kume (Osaka University, Institute of Social and Economic Research (ISER), 2008)
We examine generational differences in risk-taking behavior by means of a laboratory experiment with monetary incentives. We estimate the parameterized models in the framework of cumulative prospect theory and examine the risk aversion, probability weightings and reference point adoption of elderly and young groups. The results of our experiment indicate that the elderly group is less sensitive to changes in probability and tends to underestimate large probabilities and overestimate small probabilities more strongly than does the young group. Furthermore, we find that the elderly update their reference point after gains and tend to derive their utility from gains and losses not from levels of wealth. In sum, we find that the elderly group's behavior departs more from the traditional expected utility theory than does the young group's behavior.
Keywords: C91; D81; 330; age; cumulative prospect theory; risk aversion; probability weights; reference point